Multi-metric Conservation Assessment for the Imperiled Clinch Dace - Michael James Moore; Donald J. Orth; Eric M. Hallerman (Southeastern Fishes Council Proceedings, 2018)
Planning frameworks allow managers to spatially prioritize actions to promote species conservation. Traditional aquatic conservation planning frameworks are often organized at the ecological community or ecosystem level, which often neglect imperiled taxa occupying species-poor assemblages. In this study, we develop a multi-metric conservation assessment for the 15 geographically distinct candidate conservation areas (CCAs) occupied by the imperiled Clinch Dace (Chrosomus sp. cf. saylori). Clinch Dace habitat is threatened by anthropogenic landscape alterations, especially for coal mining and timber harvest. Our framework used four metrics to assess the conservation value of each subpopulation of Clinch Dace namely: “habitat condition”, “viability”, conservation “opportunity” and conservation “feasibility”. Occupancy models were used to determine the most influential habitat variables to Clinch Dace presence and habitat data collected for each occupied stream were used to score habitat condition in each CCA. Clinch Dace survey data were used to assess demographic population viability to highlight areas where Clinch Dace are most likely to persist. Next, we used the metrics of opportunity and feasibility to identify opportunities for reclamation as well as landownership patterns that may be bridges or barriers to conservation action. Habitat condition and viability varied among our 15 CCAs and highlighted opportunities for specific management actions including habitat conservation in some watersheds and needs for restoration in others. The feasibility metric showed that variation exists in the average lot-parcel size along occupied stream reaches, which may affect the success of some conservation actions. We recommend that managers utilize the data summarized in this study, along with stakeholder input, in a structured-decision making approach to develop specific outreach and management plans targeted to stakeholders in individual watersheds and provide an example of such a framework.
Keywords: Conservation planning; species conservation; imperiled species; aquatic habitat management; stakeholder assessment